Biosecurity and Open-Source Biology: The Promise and Peril of Distributed Synthetic Biological Technologies. - Evans, Nicholas; Selgelid, Michael (Science & Engineering Ethics, 2015)
In this article, we raise ethical concerns about the potential misuse of open-source biology (OSB): biological research and development that progresses through an organisational model of radical openness, deskilling, and innovation. We compare this organisational structure to that of the open-source software model, and detail salient ethical implications of this model. We demonstrate that OSB, in virtue of its commitment to openness, may be resistant to governance attempts.